2010
DOI: 10.5130/ajceb.v10i1/2.1592
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Building Construction Projects in Ghana

Abstract: This study investigates the causes of delay of building construction projects in Ghana to determine the most important according to the key project participants; clients, consultants, and contractors. Thirty-two possible causes of delay were identified from the literature and semi-structured interviews of 15 key players in the implementation process. These delay factors were further categorised into nine major groups. The list of delay causes was subjected to a questionnaire survey for the identification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 8 publications
(13 reference statements)
9
98
1
1
Order By: Relevance
“…The study revealed some reasons for delayed payments to include poor planning and bureaucracy on the part of the employer. This confirms earlier studies by Fugah and Agyarkwa [2] and Badu et al [18] about untimely payment of certificate by clients. The survey indicated that cash flow is a major challenge based on the contractors experience in an interview.…”
Section: Financial Challengessupporting
confidence: 82%
See 2 more Smart Citations
“…The study revealed some reasons for delayed payments to include poor planning and bureaucracy on the part of the employer. This confirms earlier studies by Fugah and Agyarkwa [2] and Badu et al [18] about untimely payment of certificate by clients. The survey indicated that cash flow is a major challenge based on the contractors experience in an interview.…”
Section: Financial Challengessupporting
confidence: 82%
“…The performance of the public sector contracts in relation to effective and efficient financing of public sector projects has been the challenge of the sector over a period with successive governments. The potential reasons for construction delays of public projects has been due to untimely honoring of certificate by client, credit inaccessibility by contractors and price fluctuations [2]. Badu et al [18] confirmed this by stating that both large and small-scale contractors experience difficulty in accessing funds.…”
Section: Literature Reviewsupporting
confidence: 49%
See 1 more Smart Citation
“…Besides, they have been experiencing delay because of procurement delay and late delivery of materials and equipment, and lack of skilled labor [41]. South Africa and Tanzania have similar issues like Ghana to produce project delay.…”
Section: Cmentioning
confidence: 99%
“…Beyond these groups, financial, managerial, government rules and regulations, and external factors were recognized as the common groups in most of the studies (Table 1). However, few studies added some more groups like contract documents or contractual relationships, design related, and environmental factors [41,51]. Based on these findings, this study classified the delay factors under 8 major groups, for example, financial, owner, contactor, consultant, manpower and resources, project, managerial, and external [4,12,47].…”
Section: Cmentioning
confidence: 99%